2021
DOI: 10.15294/elt.v10i1.40558
|View full text |Cite
|
Sign up to set email alerts
|

Students' perception toward gamification applied in English language classroom

Abstract: This study aims to find out the students' perception toward gamification applied on English language Classroom. Gamification emerged as an innovation in classroom teaching. The basic concept is to incorporate game elements into teaching, taking advantage of students' interest in games that can be used for the purposes of the teaching process. This study is conducted since there is still limited research that is conducted in Indonesia which analyses the students' perception toward the gamification utilization. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 7 publications
1
4
0
Order By: Relevance
“…In an ideal one, a teacher is ready and 100% motivated to give their best and students are 100% interested, eager to listen and understand, they are focused and do everything they are told. In reality, though, there are many factors that influence the whole process [13].…”
Section: Discussionmentioning
confidence: 99%
“…In an ideal one, a teacher is ready and 100% motivated to give their best and students are 100% interested, eager to listen and understand, they are focused and do everything they are told. In reality, though, there are many factors that influence the whole process [13].…”
Section: Discussionmentioning
confidence: 99%
“…Carrión Candel et al's (2021) paper concludes that motivation and student performance improved in the music classroom. The advantages of gamification have also been tested in the EFL classroom to encourage participation and language production (Putra & Priyatmojo, 2021).…”
Section: Literature Reviewmentioning
confidence: 99%
“…In the study on gamification in language classes, Stocker (2020) reached data supporting that gamification increased students' autonomy, competence, and emotional and behavioral engagement. Putra and Priyatmojo (2021) found that students had positive feelings towards gamification elements in foreign language classes , decreasing boredom and creating a fun environment. This popularity of gamification in learning and teaching is due to the apparent change between the generations.…”
Section: Introductionmentioning
confidence: 96%
“…After admitting the relationship between Gen Z and their specific need for technology in classrooms, this study aims at determining the effectiveness of gamification applications and LMS use (to support game-like tasks) in online 5 th -grade English lessons. Studies in the literature support the positive effects of gamification in foreign language lessons in face-to-face classrooms (Kayseroğlu & Samur, 2018;Stocker, 2020;Putra & Priyatmojo, 2021;Veljković Michos, 2017). Few studies investigate gamification in English classes during emergency remote teaching (ERT).…”
Section: Introductionmentioning
confidence: 98%